2019
DOI: 10.1029/2019gl085214
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Approach to Modeling Tidal Creek Evolution: Exploring Environmental Influences on CreekTopologies Through Ensemble Predictions

Abstract: A numerical tool integrating hydrodynamics, vegetation growth, stochastic selection, and Monte-Carlo simulation is developed to predict channel network evolution in a newly inundated backbarrier wetland. Focusing on the formation and evolution of tidal channels, model simulations suggest a clear tendency towards specific creek topologies with high probability despite creek evolution being subject to random perturbations. These creek topologies are primarily determined by wetland topography while the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In order to accelerate the evolution of landforms and make the evolution results more natural, this model uses an initial disturbance of 0.1 m terrain. According to Li et al' s research, although tidal flats evolve under random disturbance, there is still a clear trend of evolution to a specific topology, and it has a high probability [8]. In this study, the geomorphic acceleration factor is 73, and the geomorphic evolution lasts for 3 years.…”
Section: Parameter Settingmentioning
confidence: 60%
“…In order to accelerate the evolution of landforms and make the evolution results more natural, this model uses an initial disturbance of 0.1 m terrain. According to Li et al' s research, although tidal flats evolve under random disturbance, there is still a clear trend of evolution to a specific topology, and it has a high probability [8]. In this study, the geomorphic acceleration factor is 73, and the geomorphic evolution lasts for 3 years.…”
Section: Parameter Settingmentioning
confidence: 60%
“…The evolution of tidal flats and salt marshes is strongly related to tidal channel dynamics. Both tidal channel and intertidal platform evolution are governed by the interactions between hydrodynamics, sediment transport, morphological changes, and biological effects (Alizad, Hagen, Morris, Bacopoulos, et al., 2016; D'Alpaos et al., 2007; De Swart & Zimmerman, 2009; Gong et al., 2018; Li et al., 2019; Temmerman et al., 2007; Vandenbruwaene et al., 2011; Zhao et al., 2019). The mutual feedbacks (either positive or negative), which characterize these interactions, control the so‐called Morphodynamic Loop (Coco et al., 2013; Cowell & Thom, 1994; Wright & Thom, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Tidal channel networks are typical morphological features of coastal landscapes. They promote exchange of materials (water, sediments, nutrients, biota) between coastal marshes and the open sea, hence maintaining the structure and function of salt marshes (Vandenbruwaene et al 2012;Kearney and Fagherazzi 2016;Li et al 2019). A comprehensive understanding of the initial formation and long-term evolution of channel networks is fundamental to address their response to climate change and human interference (Kearney and Fagherazzi 2016;Schwarz et al 2018).…”
mentioning
confidence: 99%
“…Previous studies revealed that the formation, deepening, and expansion of channel networks are facilitated with high tidal ranges and low water depths (Kirwan and Guntenspergen 2010;Stefanon et al 2010;Van Maanen et al 2013). There is, however, growing recognition that vegetation-landform interactions play a key role in shaping intertidal landscapes (Coco et al 2013;Vandenbruwaene et al 2013;Schwarz et al 2018), although some studies suggest that the influence of vegetation is only secondary (Li et al 2019). In general, several numerical model studies have reported enhanced channel formation due to vegetation in early stages of development (D'Alpaos et al 2007;Schwarz et al 2014;Bij de Vaate et al 2020), but they did not consider later stages of channel evolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation